Organización Contable al comercial A.S. de la Ciudad de Loja, Período Enero-Marzo 2016 - Jiménez Cuenca, Enma Margarita (2016)
The thesis work entitled "ACCOUNTING ORGANIZATION TO COMMERCIAL A.S. OF THE CITY OF SHOP, PERIOD JANUARY - MARCH 2016 ", aims to propose an accounting organization that allows its owner to know the real economic and financial situation of the company, which was carried out by the execution of each one the specific objectives proposed: An accounting plan and manual was prepared according to the needs and nature of the company, for which assets, liabilities, assets, income, costs and expenses are established with their description and their respective coding, which will enable them to be identified during the accounting process. An initial inventory was made with the physical verification of each of the articles to determine the assets, rights and obligations and to make known in general the patrimony with which the company currently has. The respective auxiliary sales records were designed detailing the transactions carried out in cash or credit, payment roles, the detail of the income and expenses that each worker receives monthly and the list of provisions shows the provisions for each employee for benefits Which facilitates the simplification of the commercial movements of the commercial. The accounting process was developed through the permanent inventory control system; It was necessary to carry out an Initial Inventory in which the assets, rights and obligations cost, the Initial Statement of State that reflects the Initial Assets, Liabilities and Assets, the daily operations in the Daily Book, the registration of each of the accounts with The respective balances in the General Ledger, the transfer of amounts and balances to the Check Balance, the completion of the Worksheet with respective adjustments, Income Statement containing income, costs and expenses, the Statement of Financial Position, contains The assets, liabilities and equity accounts and the profit or loss generated at the end of the fiscal year, the Statement of Cash Flow shows the cash originated and applied during a period by the company in operating, investing and financing activities, Way to know the real economic-financial situation of the commercial. After having carried out the accounting process, the most relevant conclusions and recommendations of the whole work are described, which constitute an important tool for the owner in the decision making, with the purpose of contributing to the development and improvement of the commercial.